Kierkegaard and the treachery of love - Hall, Amy Laura (Cambridge studies in religion and critical thought, 2002)
This is a major study of Kierkegaard and love. Amy Laura Hall explores Kierkegaard's description of love's treachery, difficulty, and hope, reading his Works of Love as a text that both deciphers and complicates the central books in his pseudonymous canon: Fear and Trembling, Repetition, Either/Or, and Stages on Life's Way. In all of these works, the characters are, as in real life, complex and incomplete, and the conclusions are perplexing. Hall argues that a spiritual void brings each text into being, and her interpretation is as much about faith as about love. In a style that is both scholarly and lyrical, she intimates answers to some of the puzzles, making a poetic contribution to ethics and the philosophy of religion.